Teaching Home Environmental Health to Resident Physicians - Zickafoose, Joseph S. (Association of Schools of Public Health, 2011)
Healthy Homes programs seek to integrate the evaluation and management of a multitude of health and safety risks in households. The education of physicians in the identification, evaluation, and management of these home health and safety issues continues to be deficient. Healthy Homes programs represent a unique opportunity to educate physicians in the home environment and stimulate ongoing, specific patient-physician discussions and more general learning about home environmental health. The Case Healthy Homes and Patients Program addresses these deficiencies in physician training while providing direct services to high-risk households. Pediatric and family practice resident physicians participate in healthy home inspections and interventions for their primary care patients and follow up on identified risks during health maintenance and acute illness visits.